Likelihood of Addressing People's Tenurial Problems at State Own Enterprise Assets - Syska Naomi Hutagalung; Ima Mayasari (Universitas Negeri Semarang, 2023)
This qualitative study aimed to describe potential settlements of community's land problems on state-owned enterprises’ assets. To this end, a qualitative approach was applied. Data were garnered by reviewing literature from journal articles, online media, regulations, and reports relevant to the research topic. Data were analyzed using an interactive model comprising data collection, data reduction, data display, and drawing of conclusion. The finding revealed a number of land-related problems in SOEs’ assets. The first problem is related to people's one-sided occupation of SOEs’assets, people’s one-sided occupation of the past land, dual certificate issues between the government and the community, dual recordings between SOEs and Regional government, and customary land claim upon the state’s land. Efforts in resolving these issues also face high barriers, including hindrances in object write-off and subject nomination, inefficient court-based conflict settlement, the bad precedent of SOEs’ asset release, and an indication of post-certification trades. In this regard, some potential settlement mechanisms were proposed, including the release of fixed assets by reducing the state’s equity capital, asset utilization cooperation, the granting of land rights upon the Right of Management, and other agreement-based options. This study's findings gave implications for future policies related to the settlement of SOEs’ land problems.